Analisis Risiko Operasional Pada Proses Pembuatan Kerupuk Udang Sanah Kabupaten Tanjung Jabung Barat - Randa Aslam Putra; Rafidah Rafidah; Saijun Saijun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The importance of knowledge about operational risks for umkm partners in order to be able to control or handle the risks that must be handled and be able to solve the problems being faced, so this research aims (1) to find out the identification of operational risks in the process of making Sanah shrimp crackers in West Tanjung Jabung district ( 2) to find out the operational risk analysis of the process of making Sanah shrimp crackers in West Tanjung Jabung district, (3) to find out the efforts made by umkm actors to overcome operational risks. This research uses qualitative methods in this research using data sources obtained from the owner of the Sanah shrimp cracker business and the Sanah shrimp cracker employees. The results of this research are: In identifying operational risks, there are four types of risks as follows: human resource risks include risks of events such as unsuccessful steaming, unsuccessful cutting of crackers, long frying of crackers, failed packaging and inadequate training. Technological risks include inappropriate machines and packaging equipment that does not function properly. As well as process risks, there are risks from raw materials that do not match the dosage. And external risks include risks such as unstable raw materials and uncertain weather factors. The risk analysis that occurs in Sanah shrimp crackers has a risk level of high, medium and low. As for the aspects included in the high category, there are three risks, namely inadequate training, inappropriate packaging equipment and raw materials that do not match the measurements. And there are also medium level operational risks including unsuccessful steaming, frying for too long, inappropriate machines, unstable raw materials, weather factors that result in long drying. And there are also two levels of low risk, namely cutting crackers, failed packaging. Efforts to overcome operational risks that occur in the Sanah shrimp cracker business include requiring or providing training to employees about managing shrimp crackers and employees also need to have self-awareness to be more skilled and more thorough.